Un asesinato musical : un caso barroco - Gur, Batya; Corniero, María; Gur, Batya (Madrid : Siruela, 2014)
Detective Michael Ohayon investigates two murders in the world of classical music in Jerusalem. The victims are two musicians, a father and son, and the crime is connected to a recently discovered requiem by Vivaldi.
Online resource; title from ePub title page (Digitalia, viewed April 8, 2016)
Keywords: Ohayon, Michael -- (Fictitious character) -- Fiction; Psychoanalysts -- Fiction; Police -- Israel -- Fiction; Israel -- Fiction; Psychological fiction; Detective and mystery fiction; Electronic books